Critical role of tristetraprolin and AU‐rich element RNA‐binding protein 1 in the suppression of cancer cell growth by globular adiponectin - Nirmala Tilija Pun; Amrita Khakurel; Aastha Shrestha; Sang‐Hyun Kim; Pil‐Hoon Park (FEBS Open Bio, 2018)
Adiponectin exhibits potent antitumor activities. Herein, we examined the molecular mechanisms underlying suppression of tumor growth by globular adiponectin (gAcrp). We demonstrated that gAcrp suppressed B‐cell lymphoma 2 (Bcl‐2) expression, an anti‐apoptotic gene, by inducing its mRNA destabilization, which was accompanied with a decrease in cell viability and increased caspase‐3 activity in hepatic cancer cells. In addition, gAcrp increased expression of tristetraprolin (TTP) and AU‐rich element RNA‐binding protein 1 (AUF1), which are mRNA stability regulatory proteins. Moreover, gAcrp‐induced suppression of Bcl‐2 expression was abrogated by knockdown of TTP or AUF1. These data indicate that gAcrp induces apoptosis of hepatic cancer cells by TTP‐ and AUF1‐mediated Bcl‐2 mRNA destabilization, and further suggest that TTP and AUF1 are novel targets mediating the antitumor activity of adiponectin.